2014
DOI: 10.1111/jpi.12121
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal antioxidant treatment with melatonin to decrease newborn neurodevelopmental deficits and brain injury caused by fetal growth restriction

Abstract: Fetal intrauterine growth restriction (IUGR) is a serious pregnancy complication associated with increased rates of perinatal morbidity and mortality, and ultimately with long-term neurodevelopmental impairments. No intervention currently exists that can improve the structure and function of the IUGR brain before birth. Here, we investigated whether maternal antenatal melatonin administration reduced brain injury in ovine IUGR. IUGR was induced in pregnant sheep at 0.7 gestation and a subset of ewes received m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
167
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(191 citation statements)
references
References 54 publications
(81 reference statements)
11
167
1
7
Order By: Relevance
“…All in all, NADPH oxidase, LDL, and SERPINA1 are all associated with oxidative stress, which plays an important role in the pathological changes observed in FGR placentas. Several studies have suggest that using antioxidants (e.g., vitamins C and E) to treat pregnancies that are at high risk of FGR have shown positive effects of reducing the incidence of maternal disease and improving the prognosis of fetuses with FGR [43,44,45]. …”
Section: Discussionmentioning
confidence: 99%
“…All in all, NADPH oxidase, LDL, and SERPINA1 are all associated with oxidative stress, which plays an important role in the pathological changes observed in FGR placentas. Several studies have suggest that using antioxidants (e.g., vitamins C and E) to treat pregnancies that are at high risk of FGR have shown positive effects of reducing the incidence of maternal disease and improving the prognosis of fetuses with FGR [43,44,45]. …”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that FGR causes white matter injury in the term (late-onset) ovine FGR brain [20] , therefore we initially used Luxol Fast Blue staining as a general marker to qualitatively assess global myelin structure and demyelination, and to assign areas of interest. For Luxol Fast Blue staining, sections were dewaxed and cleared in serial ethanol before staining in a solution of Luxol Fast Blue MBSN (0.1% w/v, Aldrich), 10% acetic acid, and ethanol (95%) overnight at 60 ° C. Sections were rinsed in 95% ethanol and differentiated in 0.05% lithium chloride solution followed by 70% ethanol.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…On imaging, the FGR infant brain shows reduced total brain volume and grey matter volume [11] , and reduced hippocampal and cerebellar volume [13][14][15][16] , which might be contributed by neuronal cell loss [17] or delayed cellular complexity. Animal models of FGR, predominantly late-onset FGR, demonstrate white matter deficits as evidenced by delayed myelination [18,19] , hypomyelination, and reduced total white matter volume [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…For the fetal or neonatal brain, melatonin has a number of additional important properties. It readily crosses the placenta and the blood-brain barrier and it does not have any apparent adverse effect for the mother or baby, even in high concentrations [29,30,31]. …”
Section: Prenatal Therapiesmentioning
confidence: 99%
“…Melatonin administration to pregnant sheep mitigates the brain production of hydroxyl radical and cellular lipid peroxidation in response to acute fetal hypoxia [31]. Antenatal melatonin decreases white-matter brain injury characterized by hypomyelination and axonal damage and improves motor and cognitive function in newborn lambs after experimental intrauterine growth restriction in sheep [29]. …”
Section: Prenatal Therapiesmentioning
confidence: 99%